GAMBARAN KEJADIAN KEGAGALAN ANESTESI SPINAL PADA PASIEN SEKSIO SESAREA DI RUMAH SAKIT UMUM DAERAH ARIFIN ACHMAD PROVINSI RIAU PERIODE MEI- JUNI 2014 - Hardiyani, Wiwi Hardiyani; Irawan, Dino; Fauzia, Dina (Jurnal Online Mahasiswa (JOM) Bidang Kedokteran, 2014)
Sectio Cesarea is a birth giving of fetus through transabdomen insition in uterus or fetus excretion through the wall of abdomen insition (laparatomy) and the wall of uteus (hysterectomy). In birth giving of this sectiocesarea, the technic that is generally used is the general and regional anaesthesia, but mostly used is the regional one, especially for spinal anaesthesia. The spinal anaesthesia technic has a risk of failure that is known as failed spinal anaesthesia. The type of this research is the descriptive one with cross sectional approach, to see the description of a failed spinal anaesthesia incident to medical patient of section cesarean in General Hospital Arifin Achmad Riau Province on May-June 2014. The result of this research shows that the number of failed spinal anaesthesia incident to medical patient of section cesarean in General Hospital Arifin Achmad Riau Province is 3,4% for 3 cases. The most cause distribution are obtained by a-not-really-good medicine quality for 2 cases (66,67%), followed by unappropriate chemicals for the medicine for 1 case (33,33%). The implementation of pasca failed spinal anaesthesia in every case of this failure is the repetation of spinal anaesthesia procedure.Key words : Spinal anaesthesia, Failed Spinal Anaesthesia, Sectio Cesarea